Bibliometric analysis of medicine-related publications on poverty (2005–2015) - Sweileh, Waleed M. (Springerplus, 2016)
BACKGROUND: Poverty is a global problem. The war against poverty requires not only financial support, but also poverty-related research to pinpoint areas of high need of intervention. In line with international efforts to fight poverty and negative consequences, we carried out this study to give a bibliometric overview of medicine-related literature on poverty. Such a s study is an indicator of the extent of interaction of various international key players on the war against poverty-related health problems. METHODS: Scopus was used to achieve the objective of this study. The time span set for this study was 2005–2015. Poverty-related articles under the subject area “Medicine” were used to give bibliometric indicators such as annual growth of publications, international collaboration, highly cited articles, active countries, institutions, journals, and authors. RESULTS: The total number of retrieved articles was 1583. The Hirsh-index of retrieved articles was 56. A modest and fluctuating increase was seen over the study period. Visualization map of retrieved articles showed that “HIV”, infectious diseases, mental health, India, and Africa were most commonly encountered terms. No significant dominance of any particular author or journal was observed in retrieved articles. The United States of America had the largest share in the number of published articles. The World Health Organization and Centers for Disease Prevention and Control were among top active institutions/organizations. International collaboration was observed in less than one third of publications. Top cited articles focused on three poverty-related health issues, mainly, infectious diseases, malnutrition, and child development/psychology. Most of top articles were published in high impact journals. CONCLUSIONS: Data indicated that articles on poverty were published in high influential medical journals indicative of the importance of poverty as a global health problem. However, the number publications and the extent of international collaborations was lower than expected given the huge burden of poverty-related health problems.